Little Mouse gets ready : a toon book - Smith, Jeff, 1960 Feb. 27- (New York : Toon Books, 2009)
Little Mouse gets dressed so he can go to the barn with his mother, brothers, and sisters.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
Booklist, August 2009
Horn Book, April 2010
Kirkus Review, August 2009
Keywords: Clothing and dress -- Comic books, strips, etc. -- Juvenile fiction; Mice -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Clothing and dress -- Fiction; Mice -- Fiction; Clothing and dress -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Mice -- Comic books, strips, etc. -- Fiction; Graphic novels; Readers (Elementary).